2019
DOI: 10.1037/amp0000562
|View full text |Cite
|
Sign up to set email alerts
|

Content analysis of psychological research with lesbian, gay, bisexual, and transgender people of color in the United States: 1969–2018.

Abstract: This article updates previous content analyses that identified a relative paucity of U.S.-based psychological research on lesbian, gay, bisexual, and transgender (LGBT) people of color by extending the period covered to 2018. In addition to documenting how many such studies occurred and when, it considers the research questions asked, funding sources, impact, and journal outlets. This richer description of this research area allowed us to describe historically not only when LGBT people of color in the United S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 67 publications
2
29
0
Order By: Relevance
“…Over the past 10 years, there has been a marked increase in published studies focusing on LGB POC (Barnett et al, 2019). Despite previous evidence linking emotion-focused coping with mental health outcomes (Bandermann & Szymanski, 2014; Ngamake et al, 2016; Ouch & Moradi, 2019), few studies have identified specific emotion-focused coping strategies that LGB POC use to deal with heterosexism and racism and which strategies appear to be most effective in protecting mental health.…”
Section: Discrimination and Lgb Poc Mental Healthmentioning
confidence: 99%
“…Over the past 10 years, there has been a marked increase in published studies focusing on LGB POC (Barnett et al, 2019). Despite previous evidence linking emotion-focused coping with mental health outcomes (Bandermann & Szymanski, 2014; Ngamake et al, 2016; Ouch & Moradi, 2019), few studies have identified specific emotion-focused coping strategies that LGB POC use to deal with heterosexism and racism and which strategies appear to be most effective in protecting mental health.…”
Section: Discrimination and Lgb Poc Mental Healthmentioning
confidence: 99%
“…Further, LGBTQ stigma, discrimination, and prejudice interacts and intersects with other societal advantages or disadvantages, such as race, ethnicity, culture, geography, gender, religion, ability, and age (Mink et al, 2014;WHO, 2016). As such, the paradigm of intersectionality is appearing more in the literature, with a focus on LGBTQ people of color in the United States being a welcome addition to scholarly efforts over the past decade (e.g., Barnett et al, 2019). Proponents of intersectionality encourage scholars to conceptualize the needs of sub-groups within social categories, and how individuals' needs manifest through the inhabitation of multiple salient identity statuses (e.g., being LGBTQ, a person of color, and an immigrant).…”
Section: Intersectionalitymentioning
confidence: 99%
“…Inclusivity, on the other hand, is reflected by peoples' perceptions, such as feeling "at home," feeling free to openly express themselves, feeling that their ideas are valued, and that they can meaningfully contribute to the organization. These considerations are key for underrepresented people seeking to participate and sustain their participation in organizations, academic institutions, and businesses [7,[14][15][16][17][18][19][20].…”
Section: Why Diversity and Inclusion And What's The Difference?mentioning
confidence: 99%